Peran Pendidikan Dalam Keputusan Bekerja di Sektor Pertanian pada Masa Pandemi Covid-19 - Fitriani Aditya Putri; Priscilia Calista; Miftahul Jannah; Eva Eva; Ahmad Yani (Seminar Nasional Official Statistics, 2022)
The agricultural sector is one sector that is able to survive when the economic contraction in Indonesia during the Covid-19 pandemic. This study aims to assess the impact of educational attainment on their decision to work in the agricultural sector during the pandemic for lost-jobs workers due to the Covid-19 pandemic. Based on estimates using binomial logistic regression, the results show that the lower the educational attainment of lost-jobs workers due to the Covid-19 pandemic, the higher their tendency to work in the agricultural sector. Therefore, agricultural sector is a promising sector which does not require unspecific skill for lost-job workers.